ANALISIS NUTRISI DAN ANTIOKSIDAN UMBI MENTAH DAN KUKUS DARI GANYONG (Canna edulis Kerr.) KULTIVAR LOKAL LEMBANG - Triani, Rini; Marthia, Nabila; Nurhawa, Shalli; Siti Nurminabari, Ina (Department of Food Technology, Universitas Pasundan, Bandung, 2023)
This study aims to analyze the nutritional and antioxidant content of raw and cooked canna tubers (steamed) of the local Lembang cultivar, agricultural products of Pasir Angling, Suntenjaya Village, Lembang District, West Bandung Regency. The method used is chemical analysis to determine the content of nutritional values of the tuber such as carbohydrates, proteins, fats and also the total antioxidant content (DPPH). The results showed that canna steamed tubers had higher nutritional and antioxidant content compared to raw tubers. This shows that the cooking process can affect the content of nutrients and antioxidants in canna tubers. Consequently, Ganyong steamed tubers can be considered as a source of nutrients and antioxidants that are beneficial to human health.